Free Radical Scavenging Activity of 2,2-diphenyl-1-picrylhydrazil from Ethanolic Extract of Salam Leaves (Syzygium polyanthum) - Erma Yunita; Andi Wijaya (Jurnal Farmasi Ma Chung: Sains, Teknologi, dan Klinis Komunitas, 2026)
Syzygium polyanthum (Salam) leaves are widely utilized as both a culinary spice and a traditional medicinal plant in Indonesia. They are rich in phenolic compounds, which are known to exhibit potent antioxidant properties. This study aimed to quantitatively evaluate the in vitro antioxidant activity of the ethanolic extract of S. polyanthum leaves. The antioxidant capacity was determined using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay via visible spectrophotometry. The extract was tested at concentrations ranging from 12.5 to 200 ppm, with ascorbic acid serving as the positive control. The median inhibitory concentration (IC50) was calculated using linear regression analysis. The DPPH radical exhibited a maximum absorption wavelength (lmax) at 517.8 nm. The ethanolic extract of S. polyanthum leaves demonstrated a concentration-dependent radical scavenging activity, achieving 95.27 ± 0.17 % inhibition at 200 ppm. The calculated IC50 value for the extract was 36.37 ± 6.02 ppm, whereas the ascorbic acid standard exhibited an IC50 of 1.36 ± 0.08 ppm. According to the standard antioxidant potency classification, the ethanolic extract of S. polyanthum leaves falls into the "very strong" antioxidant category (IC50 < 50 ppm). These findings suggest that S. polyanthum leaves represent a highly promising natural source for the development of functional antioxidant products.